Analisis Kesesuaian Program Keberagamaan Siswa SMP dengan Tahapan Perkembangan Psikologis Remaja - Ariska, Mutiara; Koestanti, Melinda; Prilianto, Figo; Arjuna, Arjuna; Suhartini, Andewi (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
This article examines various forms of religious education programs for Junior High School (SMP) students and analyzes their alignment with psychological and spiritual developmental stages in early adolescence. Employing a literature review approach, this study explores theories of faith development (James W. Fowler), cognitive development (Jean Piaget), and moral development (Lawrence Kohlberg), alongside key concepts in Islamic education such as fitrah, taklīf, and ta’dīb. The findings indicate that religious programs in SMP generally encompass daily worship habituation, spiritual mentoring, collective religious activities, the integration of spiritual values across subjects, and project-based reflective activities. The effectiveness of these programs heavily relies on the alignment between program design and students' developmental characteristics. Ritualistic and collective approaches assist in building routines and social identity, whereas reflective and dialogical approaches foster deeper spiritual awareness. Challenges encountered include limited time, teacher preparedness, student interest, and the consistency of school culture.